2019 Portland International Conference on Management of Engineering and Technology (PICMET) 2019
DOI: 10.23919/picmet.2019.8893715
|View full text |Cite
|
Sign up to set email alerts
|

Operationalising Ambidexterity: The Role of "Better" Management Practices in High-Variety, Low-Volume Manufacturing

Abstract: Innovation and change are fundamental to the long-term sustainability of any organisation. Whilst it is important to improve operating efficiency in the bid to become more cost competitive, there is still an underlying need to venture out of the norm and explore new opportunities. Though a great deal of research has emerged regarding the achievement of ambidexterity, there remains a gap in understanding how this is actually operationalised in organisations. This paper takes aim at this problem in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Finally, this paper also substantiates the conceptual arguments presented in Katic et al (2019) concerning the potential for BMP to help HVLV manufacturers in deploying ambidexterity. Building off the apparent bias towards exploitation in HVLV manufacturing literature (Katic and Agarwal, 2018), we extend these contributions by empirically demonstrating the dual nature of capability investments in both ambidexterity and BMP towards both exploratory (process innovation) and exploitative (operational flexibility) performance outcomes.…”
Section: Ambidexterity Through Better Management Practicessupporting
confidence: 77%
“…Finally, this paper also substantiates the conceptual arguments presented in Katic et al (2019) concerning the potential for BMP to help HVLV manufacturers in deploying ambidexterity. Building off the apparent bias towards exploitation in HVLV manufacturing literature (Katic and Agarwal, 2018), we extend these contributions by empirically demonstrating the dual nature of capability investments in both ambidexterity and BMP towards both exploratory (process innovation) and exploitative (operational flexibility) performance outcomes.…”
Section: Ambidexterity Through Better Management Practicessupporting
confidence: 77%
“…This is relevant because there is also a gap in the literature about the key elements regarding the BMI process [26]. There are few studies dealing with ambidexterity processes for BMI [21], and an operational approach on how can SMEs perform it not clear in the literature. This is in line with recent studies that do highlight the importance of ambidexterity for the innovativeness of SMEs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Organizational ambidexterity has also been often highlighted as a mechanism to attain sustainability [19,20]. However, this is another concept that is difficult to implement [21]. Again, in the context of SMEs, it becomes an even more difficult task [12], even though, as suggested by recent studies, SMEs could benefit from being ambidextrous and should take action in this direction [22].It is observed that, although BMI and ambidexterity are important mechanisms for achieving sustainability, the connection between both concepts has received limited attention in the literature [23].…”
mentioning
confidence: 99%
“…However, the performance measurement process can serve other functions within the ambit of the control process. Katic and Bevanda (2019) stated that aside from the provision of insights, performance measurement might clarify the objectives of the organisation's management to the lower levels of the organisations. Looy and Shafagatova (2016) outlined the fundamentals of performance measurement as alignment of measures of performance with adopted strategies of the organisation; measures in sub-unit aggregating into wide measures of the organisation; measurement regime commitment; performance having effect from measurement; and reliability of measures.…”
Section: 7mentioning
confidence: 99%